Synthesis of Bipyridine Ether-Type Bifunctional Precursors - Bálint Jávor; Antal Agárdi; Péter Kisfaludi; Barnabás Frigyes; Márton Temesvári; Panna Vezse; Tünde Tóth; Péter Huszthy; Ádám Golcs (Organics, 2025)
Bipyridine ethers are commonly occurring structural motifs in supramolecular chemistry. The herein reported efforts aim to extend the synthetic platform of bipyridino-precursors with new bifunctional intermediates and to improve some previously reported synthetic strategies for structural analogues, like bipyridine-diols as common macrocycle precursors. In addition, their optimized and highly efficient oxidation to the corresponding dialdehydes is reported to obtain further reactive intermediates with wide modifiability. Furthermore, methylations of pyridine-carbaldehydes were carried out alongside different synthetic strategies to introduce chirality centers. Synthetic difficulties and some unsuccessful approaches are also reported to help in focusing future efforts.